Mul Tumbler / Muhamad Dini Danial Zamri ... [et al.] - Danial Zamri, Muhamad Dini; Ismail, Anis Shazlyn; Anuar, Nur Hamizah; Abdull Aziz, Nurhaziqa; Zulkefli, Siti Zulaika; Rushaidi, Syazwani Balqis
Our company is a new form of ownership engaged in the manufacturing industry that produces Mul Tumbler. The purpose of creating this product is to improve the customer experience and make it easier for them to make or drink hot or cold water. Our Mul Tumbler is a water heating and cooling device as well as a flask capable of holding water in a variety of conditions. It is an electric kettle advancement product with several distinct features and functions, including a rechargeable battery, LED touch screen display, temperature control, security lock, anti-spill lid, and GPS locator. The concept of this product is to make it easier for people to carry it everywhere, to create multi-functional electric kettles that can benefit consumers, to develop electric kettles with a safety lock to increase security, and to produce an electric kettle that can store and maintain water conditions for a longer period of time. Based on the product, our target market consists of people who lead hectic lifestyles, such as students, travellers, families, and those who work full-time. Our product, on the other hand, can be used by anyone because it has a variety of functions that can benefit any user. Furthermore, because our primary target market is students, we do not consider income to be our primary subject. This product will benefit consumers and attract the attention of our target market. This is due to the fact that our Mul Tumbler is a user-friendly product that saves time and is easy to use for everyone.